Assessing User Experience in Indonesian Fashion Mobile Applications Using a Usability Testing Approach - Maryani Maryani; Benny Jabriel; Emmanuel Daniel W (Diponegoro University, 2025)
The rapid growth of mobile applications in the fashion industry has transformed how consumers interact with brands, browse products, and make purchasing decisions. While previous studies have examined consumer attitudes and behaviors toward fashion mobile applications, limited attention has been given to measuring and quantifying the overall user experience (UX), particularly in emerging markets such as Indonesia. This study aims to address this research gap by assessing the user experience of fashion mobile applications through questionnaire-based usability evaluation. The research employs design principles and user interface (UI) elements as analytical frameworks to evaluate how effectively fashion mobile app designs influence engagement, navigation ease, and purchase intention among Indonesian users. Data was collected from a sample of active fashion app users and analyzed to identify key usability factors that contribute to positive or negative user experiences. The findings reveal that interface aesthetics, interaction simplicity, and personalized recommendations have a significant impact on user satisfaction and in-app purchasing behavior. The results underscore the importance of user-centered design in developing fashion mobile applications tailored to the expectations and digital habits of Indonesian consumers. This study contributes to the growing body of literature on UX evaluation in mobile commerce by providing insights into how design-driven usability influences user engagement and business outcomes in the fashion retail context.